Effect of fermentation time on phenolic content and antioxidant potential in Cupuassu (Theobroma grandiflorum (Willd. ex Spreng.) K.Schum.) beans (2017)
Cupuassu (Theobroma grandiflorum (Willd. ex Spreng.) K.Schum.) is an evergreen tree in the family Malvaceae, with nutritional qualities of interest in the food and cosmetic industry. It is necessary for its processing, in addition to other processes, to perform a fermentation, affecting its chemical composition. Therefore, the effect of fermentation time on the phenolic content and antioxidant activity of Cupuassu (T. grandiflorum) beans, was determined. During this process, the chemical properties of the beans and the phenolic content were evaluatedevery two days; also quantifying the secondary metabolites Catechin, Epicatechin, Theobromine and Caffeine by high performance liquid chromatography (HPLC). The antioxidant activity was analyzed using the ABTS, DPPH, and FRAP assays. Analysis of phenolic content and antioxidant activity showed a decrease after 6 days of fermentation. Therefore, it is not recommended to continue fermentation after this period due to a negative influence of the process on the bioactive substances (Catechins) content, and the reduction of the ability to inhibit free radicals, exhibited by Cupuassu beans.